Suppressed fat mobilization due to PNPLA3 rs738409 - associated liver damage in heavy drinkers: the liver damage feedback hypothesis - Rausch, Vanessa; Mueller, Sebastian (Alcohol and cancer, 2018)
PNPLA3 variant rs738409 has been identified as important progression factor in patients with ALD and NAFLD, the most common liver diseases worldwide. These findings point towards similarities between...